Il trauma nel tempo e nello spazio del romanzo: Perrin, Ernaux e Parrella (Comparatismi, 2025)
The article explores the theme of trauma through a comparative analysis of three novels: Cambiare l’acqua ai fiori by Valérie Perrin, L’evento by Annie Ernaux and Lo spazio bianco by Valeria Parrella. These novels represent female traumas that, starting from private experiences such as unwanted pregnancy, abortion, premature birth, the death project onto a public dimension, assuming the significance of historical and collective traumas. The analysis focuses on the relationship between time and space in the context of trauma, highlighting how trauma disrupts and shatters the individual’s identity, also reflecting in the narrative structures. Memory plays a crucial role in the process of fragmentation and alienation of the categories of time and space. The article also emphasizes how literary writing can represent and overcome trauma, allowing for a reconquest of the temporal dimension and a new self-awareness.
Keywords: Time; Space; Trauma; Novel; Birth